Faecal immunochemical test after negative colonoscopy may reduce the risk of incident colorectal cancer in a population-based screening programme. Issue 7 (28th September 2020) - Peng, Szu-Min; Hsu, Wen-Feng; Wang, Ying-Wei; Lin, Li-Ju; Yen, Amy Ming-Fang; Chen, Li-Sheng; Lee, Yi-Chia; Wu, Ming-Shiang; Chen, Tony Hsiu-Hsi; Chiu, Han-Mo
Abstract : Objective: Subjects with a positive faecal immunochemical test (FIT) have a much higher likelihood of advanced neoplasms than the general population. Whether FIT-positive subjects with negative colonoscopy should receive subsequent FIT screening remain unclear. Design: Subjects with a negative colonoscopy after positive FIT in the first screening in the Taiwanese Colorectal Cancer (CRC) Screening Program 2004–2009 were followed until the end of 2014. CRC incidence was compared between those who did and did not receive subsequent FIT screening. Cox regression analysis was conducted, adjusting for major confounders to investigate whether subsequent FIT was associated with lower risk of incident CRC. Results: The study cohort was comprised of 9179 subjects who had negative diagnostic colonoscopy after positive FIT in 2004–2009, of whom 6195 received subsequent FIT during the study period. The CRC incidence (per 1000 person years) was 1.34 in those who received subsequent FIT and 2.69 in those who did not, with corresponding adjusted HR (aHR) of 0.47 (95% CI 0.31 to 0.71). Lower adenoma detection rate of diagnostic colonoscopy was associated with higher risk of incident CRC but became non-significant in multivariable analysis after adjustment for subsequent FIT. Higher baseline faecal haemoglobin concentration (FHbC, μg haemoglobin/g faeces) was associated with increased risk of incident CRC (reference: FHbC=20–39; aHR=1.93 (1.04–3.56), 0.95 (0.45–2.00), 2.26 (1.16–4.43) and 2.44 (1.44–4.12) for FHbC=40–59, 60–99, 100–149 and ≥150, respectively). Conclusion: Subsequent FIT should be scheduled after negative colonoscopy to detect missed neoplasms and reduce the risk of incident CRC in a national FIT screening programme.